Profile of mob justice victim fatalities admitted at Polokwane Forensic Pathology Laboratory Limpopo Province - Mokoka, Madinane (My University, 2024)
Introduction and background: Community-based assault is a phenomenon practiced worldwide and it contributes to the rise in unnatural deaths due to violence. Aim: The study aimed to profile fatal mob justice victim cases admitted at the Polokwane Forensic Pathology Services Laboratory, Limpopo Province. Method: A cross-sectional descriptive quantitative study was conducted using sample size of 141 community assault death victims that were selected using consecutive sampling of community assault deaths admitted to Polokwane Forensic Pathology Services laboratory over a period of 5 years. Results: The study revealed that black male adults residing in townships suffered fatal mob justice. The main causes of death included multiple injuries, head injuries and severe soft tissue injuries. Conclusion: The profile of community assault deaths identified was similar to that of reviewed literature.
Thesis (M. Med. (Forensic Pathology)) -- University of Limpopo, 2024
Keywords: Community; Assault; Mob; Justice; Victim; Hot spot; Polokwane forensic pathology service; Criminal justice; Restorative justice; Forensic pathology; Death -- Causes; Violent deaths